2014
DOI: 10.1186/1475-2859-13-s1-s8
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of lactic acid bacteria: from food to health

Abstract: Genome analysis using next generation sequencing technologies has revolutionized the characterization of lactic acid bacteria and complete genomes of all major groups are now available. Comparative genomics has provided new insights into the natural and laboratory evolution of lactic acid bacteria and their environmental interactions. Moreover, functional genomics approaches have been used to understand the response of lactic acid bacteria to their environment. The results have been instrumental in understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 212 publications
(269 reference statements)
0
106
0
5
Order By: Relevance
“…Conjugative transposons are one of the main drivers of gene gain and loss, and therefore if the lack of transposases in strain MG1 truly reflects a low level of genome plasticity, this could indicate the stable adaptation of this strain to its sourdough niche (Douillard & de Vos, 2014;Hols et al, 2005). However, the low number of transposases in these strains of W. cibaria is in stark contrast to the 111 found in another sourdough LAB, Lactobacillus sanfranciscensis TMW 1.1304, in which it was suggested that their high number facilitated niche adaptation of this strain (Vogel et al, 2011).…”
Section: Genomics Of Weissellamentioning
confidence: 99%
“…Conjugative transposons are one of the main drivers of gene gain and loss, and therefore if the lack of transposases in strain MG1 truly reflects a low level of genome plasticity, this could indicate the stable adaptation of this strain to its sourdough niche (Douillard & de Vos, 2014;Hols et al, 2005). However, the low number of transposases in these strains of W. cibaria is in stark contrast to the 111 found in another sourdough LAB, Lactobacillus sanfranciscensis TMW 1.1304, in which it was suggested that their high number facilitated niche adaptation of this strain (Vogel et al, 2011).…”
Section: Genomics Of Weissellamentioning
confidence: 99%
“…The dominance of Lactobacillus species such as L. iners, L. jensenii, L. gasseri, and L. crispatus in the vaginal region acts as a barrier for invasion of pathogenic bacteria and virus. Lactobacillus is an indicator of a healthy vaginal ecosystem, hence their rapid identification can prove helpful in diagnosing bacterial vaginosis [19][20][21].…”
Section: The Trouble With Lactobacillus Identificationmentioning
confidence: 99%
“…lactis muestra un incremento en la producción de ácido láctico a través del tiempo, lo anterior responde a que las cepas necesitan el azúcar del medio para realizar sus funciones fisioló-gicas y como producto de la fermentación se obtiene ácido láctico [40]. El ácido láctico es producido en forma comercial como conservante de productos alimenticios, ya que inhibe el crecimiento de microorganismo en los alimentos; de igual manera, se ha observado que inhibe el crecimiento de bacterias patógenas en el tracto gastrointestinal del hospedero [41], por lo que su producción por parte de las BAl es importante.…”
Section: Cinética De Fermentaciónunclassified